Auditor’s Professional Judgement and the Emergence of Artificial Intelligence in External Auditing - Tashkovski, Filip; Zdolšek, Daniel (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Advanced technological innovation has become a defining feature of modern auditing, gradually transforming auditing procedures. The increasing adoption of technological tools (i.e., robotic process automation, data analytics etc.) is reshaping auditors’ decision-making processes, generating both significant benefits and notable risks for auditors and the auditing profession. This paper examines the growing role of technology, specifically artificial intelligence, within the auditing profession, with particular emphasis on its strengths and associated limitations, and the implications for auditors’ professional judgement. It briefly reviews auditing pronouncements regarding the use of technology in contemporary audit practice. Furthermore, the paper analyses the key problems, challenges, and opportunities auditors face when exercising professional judgement in technology-enabled audits. The discussion considers the implications of using advanced technology in an audit for auditors and their professional judgement. Also, auditors’ responsibilities and accountability are considered. The paper concludes that while technological innovation offers substantial opportunities to enhance audit efficiency and effectiveness, auditors’ professional judgement and professional scepticism remain essential to ensuring reliable and high-quality audit outcomes.